Broadband circularly polarized antenna with moon‐shaped parasitic element. Issue 5 (25th February 2016) - Sim, C. Y. D.; Hsu, Y. W.; Lin, C. W.; Yang, G.
ABSTRACT: A broadband circularly polarized (CP) circular patch antenna with an L‐shaped ground plane and parasitic element is studied. The use of this L‐shaped ground is to achieve short probe feed connection to the circular patch, while maintaining a certain height between the circular patch and ground plane, so that good impedance matching and bandwidth enhancement can be attained. To achieve CP radiation, two notches are initially loaded diagonally into the circular patch, and to further enhance the CP bandwidth, a novel technique of loading a small size moon‐shaped parasitic element into the notched circular patch is proposed. By doing so, the CP bandwidth of proposed antenna can be tremendously increased by approximately 10%. The experimental results show that the proposed CP antenna can yield impedance bandwidth and CP bandwidth of 835–1150 MHz and 839–968 MHz, respectively, with good gain level of 7.6 dBic. Therefore, this proposed wideband CP antenna can be used for UHF (ultrahigh frequency) RFID (radio frequency identification) reader antenna that operates within the universal RFID bands (840 − 960 MHz). © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:387–395, 2016